STUDY OF SECOND-ORDER LINES AND SURFACES USING THE GENERAL EQUATION (Web of Technology: Multidimensional Research Journal, 2024)
The role of geometry in the development of students' thinking and their education, as well as in the practical application of the knowledge acquired in mathematics, in the formation of skills and qualifications, is incomparable. The study of geometric objects and the correct visualization are of great importance in the formation of students' mathematical knowledge, skills and abilities at a high level. It is known that the content of the science of geometry is made up of a system of axioms, theorems, definitions and problems, and all of them together form the concepts of the science of geometry. The logical connection between the students' geometric training and their professional pedagogical training is reflected in the acquisition of mathematical knowledge by the future student of mathematics. For this reason, the parameters for determining the student's geometric readiness have been specified. Since lining is of great importance, attention was paid to the subject of second-order lines and surfaces.